Isolated descemetorhexis for anterior synechiolysis prior to endothelial keratoplasty – case report and technique - Droutsas K; Andreanos K; Lazaridis A; Georgalas I; Kymionis G; Papaconstantinou D (Dove Medical Press, 2017)
Konstantinos Droutsas,1,2 Konstantinos Andreanos,1 Apostolos Lazaridis,2 Ilias Georgalas,1 George Kymionis,1,3 Dimitris Papaconstantinou1 1First Department of Ophthalmology, National and Kapodistrian University of Athens, Athens, Greece; 2Ophthalmology Department, Philipps University Marburg, Marburg, Germany; 3Ophthalmology Department, Jules Gonin Eye Hospital, University of Lausanne, Lausanne, Switzerland Purpose: To describe the utilization of descemetorhexis for reformation of the anterior chamber in eyes with central iridocorneal synechiae before endothelial keratoplasty (EK).Methods: A 71-year-old man with a history of trabeculectomy complicated by hypotony presented with bullous keratopathy in the presence of extensive iridocorneal synechiae and a flat anterior chamber. In order to proceed with EK, synechiolysis with the use of viscoelastic and scissors was attempted. Despite successful dissection of the peripheral strands, the pupillary margin of the iris remained attached to the endothelium. Therefore, descemetorhexis was performed to detach the Descemet membrane along with central synechiae and create sufficient space for safe EK at a later stage.Results: Corneal clarity was restored by ultrathin Descemet stripping automated endothelial keratoplasty, leaving a fibrous membrane in the pupillary plane, which was excised 2 months later, allowing an improvement of best-corrected visual acuity to 0.5.Conclusion: Isolated descemetorhexis was successfully employed to reform the anterior chamber and proceed with EK in a case of bullous keratopathy and resistant iridocorneal synechiae. This stepwise approach may be considered in similar cases in order to avoid a more invasive treatment, ie, penetrating keratoplasty and synechiolysis. Keywords: endothelial keratoplasty, iridocorneal synechiae, bullous keratopathy, descemetorhexis